Validation of the Maslach Burnout Inventory - Human Services Survey to assess burnout of prison officers working in Sri Lankan Prisons - Nimali Wijegoonewardene; Janaki Vidanapathirana; Tharaka Fernando (College of Community Physicians of Sri Lanka, 2019)
Introduction: Prison officers undergo a high amount of work-stress and consequently suffer from burnout, which is detrimental to their health, the organization and the inmates. There are no studies conducted on burnout of prison officers in Sri Lanka, partly due to the non-availability of a validated scale.   Objectives: To validate the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) for assessing burnout among prison officers working in Sri Lankan prisons.   Methods: A cross-sectional validation study was carried out among a representative sample of 267 correctional and rehabilitation officers working in the Colombo Remand Prison and Colombo New Magazine Prison, selected through probability-proportionate-to-sample size and random sampling methods. The Sinhala-translated MBIHSS was judgmentally validated and pre-tested prior to administration. Confirmatory factor analysis (CFA) was performed using LISREL 9.3 software to assess the construct validity of MBI-HSS. The presence of job-related neurasthenia in participants, diagnosed by a psychiatrist was taken as the gold standard to assess the criterion validity. Internal consistency and test-retest methods were used to assess the reliability.   Results: A three-factor model with items 6, 13, 16 and 22 of the instrument deleted, was identified as the model best fitting the data during CFA, achieving the best goodness of fit parameters (RMSEA=0.0748; χ2=185.2, p=0.001; χ2/df=1.4; CFI=0.974; NNFI=0.97; GFI=0.985; SRMR=0.056). Clinical burnout was seen in 32.6% of the sample. According to the cut-off values achieved through receiver operating characteristics (ROC) curves for burnout and its three sub-scales of emotional exhaustion, depersonalization and diminished personal accomplishment, the sensitivity and specificity were 94.3% & 87.8%; 82.8% & 80.6%; 72.4% & 73.9%; and 77% & 77.2%, respectively. The reliability of the tool was satisfactory.   Conclusions: Translated and validated MBI-HSS was found to be a valid and reliable tool for assessing burnout among Sri Lankan prison officers. Using it during their medical examinations is recommended.